Expolio, expolios, expoliados - Emanuela Canghiari (Casa de Velázquez, 2021)
This is a pluri-disciplinary dossier that seeks to examine the notion of the «spoliation» of cultural wealth in Spain and in Latin America, from the colonial period through to the present. This is a polysemic phenomenon that changes throughout different historical periods, the geographical context and the kind of power relationships between the different parties involved. But it is also multi-faceted in that it has repercussions at different levels and diverse situations such as archaeological sites, museums, markets, cities, thought and identities. Spoliation is thus full of ideological, political, symbolic and even emotional implications. It certainly cannot be examined as a single phenomenon, but must be seen rather as a meeting point where many circumstances combine at once. The dossier offers eight case-studies that illustrate this complexity and bring to light its social impact as well as its different actors, those active and those that suffer spoliation.